Liquid metal-hydrogel composite radiation protection material as well as preparation method and application thereof
By combining liquid metal with hydrogel, liquid metal-hydrogel composite materials are prepared, which solves the toxicity, weight and rigidity of existing lead-based materials, and achieves a non-toxic, lightweight, flexible and efficient radiation shielding effect, suitable for flexible wearable fields.
Patent Information
- Application Number
- CN202411787351.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-12-06
AI Technical Summary
Existing lead-based radiation shielding materials have problems such as toxicity, high weight, high rigidity, and inability to effectively shield low-energy X-rays, and are difficult to be widely used in the field of flexible wearables.
Using liquid metal-hydrogel composite materials, materials with excellent biocompatibility, adjustable mechanical properties and efficient radiation shielding ability are prepared by combining metal indium, tin, bismuth and hydrogel.
It achieves a non-toxic, lightweight, flexible and effective radiation shielding effect, and is suitable for lead-free radiation protection equipment required during radiation diagnosis and treatment, providing better fit and comfort.
Smart Images

Figure CN119529322A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of radiation shielding materials, and specifically relates to a liquid metal-hydrogel composite radiation protection material and a preparation method and application thereof. Background Art
[0002] According to the World Health Organization (WHO), the medical industry is the industry with the highest utilization rate of ionizing radiation. More than 3.6 billion radiological diagnostic examinations, 37 million nuclear medicine surgeries, and 7.5 million radiotherapy treatments are performed worldwide each year. X-rays and gamma rays are often used in radiological diagnosis and treatment. Different doses of X-rays and gamma rays can cause different degrees of harm to the human body, such as skin erythema, edema, ulcers and hair loss, leukopenia, myeloma, etc., and even endanger life in severe cases. Therefore, effective radiation shielding of X / gamma rays is crucial.
[0003] In the prior art, the most commonly used radiation shielding materials are lead plates or lead-containing materials. However, lead-based radiation shielding materials have many disadvantages. First, lead is toxic, and long-term exposure may cause serious health problems such as neurological disorders and renal failure; second, traditional lead aprons are heavy and long-term wearing will affect comfort, and their rigidity limits their application scenarios in the field of flexible wearables; moreover, when the material contains only one type of high-Z element, their photon attenuation ability will gradually decrease, because as the attenuation process proceeds, the photon energy will decrease below the K or L edge, that is, the weak absorption zone of the high-Z element, and lead has a weak X-ray absorption zone in the range of 30-80keV.
[0004] Based on the above problems, there is an urgent need to develop new non-toxic, lightweight, flexible and effective radiation shielding materials as a substitute for lead. Summary of the invention
[0005] In response to the problems existing in the prior art, the present invention provides a liquid metal-hydrogel composite radiation protection material and a preparation method and application thereof. By combining the advantages of liquid metal and hydrogel, excellent biocompatibility, adjustable mechanical properties, and efficient radiation shielding capabilities are achieved, which is beneficial as a new type of lead-free radiation protection material.
[0006] In order to solve the above technical problems, the present invention is implemented through the following technical solutions:
[0007] A method for preparing a liquid metal-hydrogel composite radiation protection material comprises the following steps:
[0008] Step 1, weighing metal indium, tin and bismuth in a certain mass ratio, and placing them in a flask in order of melting point from low to high, and then adding glycerol to immerse the mixture of metal indium, tin and bismuth in the flask by 2-3 cm;
[0009] Step 2, placing the flask containing the mixture of metal indium, tin, bismuth and glycerol in an argon atmosphere for a period of time to expel air, and then continuing to stir the mixture in the argon atmosphere at a certain temperature using a heating magnetic stirrer for a period of time at a low speed, and then stirring the mixture at a high speed for a period of time, so as to cause the bulk liquid metal in the flask to become spherical liquid metal particles;
[0010] Step 3, after the bulk liquid metal in the flask is transformed into spherical liquid metal particles, the spherical liquid metal particles are taken out from the glycerol, and finally washed with water and dried to obtain liquid metal alloy particles with a particle size in the range of 50-200 μm;
[0011] Step 4, weigh polyvinyl alcohol and pure water to prepare a PVA-H2O solution with a mass fraction of 15%;
[0012] Step 5, weigh polyvinyl alcohol and DMSO to prepare a PVA-DMSO solution with a mass fraction of 15%;
[0013] Step 6: Mix the prepared PVA-H2O solution and PVA-DMSO solution in a certain mass ratio and stir evenly, then add the prepared liquid metal alloy particles in a certain mass ratio and stir evenly.
[0014] Step 7, using a high-power numerically controlled ultrasonic cleaner, ultrasonically treat the mixed solution of the PVA-H2O solution, the PVA-DMSO solution and the liquid metal alloy particles for a period of time to remove bubbles;
[0015] Step 8: Pour the mixed solution of the PVA-H2O solution with bubbles removed, the PVA-DMSO solution and the liquid metal alloy particles into an acrylic mold of a specific size, and freeze it for a period of time to form a gel, thereby obtaining a liquid metal-hydrogel composite material with a certain liquid metal content.
[0016] Furthermore, in step 1, the sum of the mass fractions of metal indium, tin, and bismuth is 100 parts, and the mass ratio of indium, tin, and bismuth is adjusted to prepare liquid metal alloy particles with different proportions. The specific mass ratios include but are not limited to the following options:
[0017] In:Sn:Bi=51:16.5:32.5, used to prepare Bi 32.5 In 51 Sn 16.5 Liquid metal alloy particles;
[0018] In:Sn:Bi=28:18:54, used to prepare Bi 54 In 28 Sn 18 Liquid metal alloy particles;
[0019] In:Sn:Bi=50:40:10, used to prepare Bi 10 In 50 Sn 40 Liquid metal alloy particles;
[0020] In:Sn:Bi=66.3:0:33.7, used to prepare Bi 33.7 In 66.3 Liquid metal alloy particles.
[0021] Furthermore, in step 2, a flask containing a mixture of metal indium, tin, bismuth and glycerol is placed in an argon atmosphere and the air is exhausted for 5 minutes. The temperature of the heating magnetic stirrer is set to 275°C, the speed of the magnetic low-speed stirring is 200 rpm, the low-speed stirring time is 30 minutes, and the speed of the magnetic high-speed stirring is 1000 rpm, and the high-speed stirring time is 5 minutes.
[0022] Further, in step 4, the preparation method of the PVA-H2O solution is:
[0023] First, polyvinyl alcohol with a molecular weight of 89000-98000 and pure water were mixed in a mass ratio of 15:85;
[0024] Then, a heating magnetic stirrer was used to stir at a temperature of 90°C and a magnetic stirring speed of 300 rpm;
[0025] After dissolution, a PVA-H2O solution with a mass fraction of 15% was obtained.
[0026] Further, in step 5, the preparation method of the PVA-DMSO solution is:
[0027] First, polyvinyl alcohol with a molecular weight of 89000-98000 and DMSO were mixed in a mass ratio of 15:85;
[0028] Then, a heating magnetic stirrer was used to stir at a temperature of 90°C and a magnetic stirring speed of 300 rpm;
[0029] After dissolution, a PVA-DMSO solution with a mass fraction of 15% was obtained.
[0030] Furthermore, in step 6, the mass ratio of the PVA-H2O solution to the PVA-DMSO solution is 4:6, and the mass ratio of the mixed solution of the PVA-H2O solution and the PVA-DMSO solution to the liquid metal alloy particles is 1:1, so as to prepare a liquid metal-hydrogel composite material with a liquid metal content of 50%.
[0031] Furthermore, in step 7, the ultrasonic time of the high-power CNC ultrasonic cleaner is 3 minutes.
[0032] Furthermore, in step 8, the freezing temperature of the mixed solution of the PVA-H2O solution, the PVA-DMSO solution and the liquid metal alloy particles is -20°C, and the freezing time is 2 minutes.
[0033] A liquid metal-hydrogel composite radiation protection material is prepared by adopting the preparation method of the liquid metal-hydrogel composite radiation protection material.
[0034] A new application of the liquid metal-hydrogel composite radiation protection material can be used as a new type of lead-free radiation protection material for manufacturing lead-free radiation protection equipment required in radiation diagnosis and treatment processes.
[0035] The beneficial effects of the present invention are:
[0036] The present invention firstly prepares liquid metal alloy particles through a simple preparation method. The liquid metal particles contain more than two elements, have a large number of electrons and multiple absorption edges. Due to the complementarity of the absorption edges, the probability of the photoelectric effect is increased, and the ability to shield photons of different energies is significantly enhanced. At the same time, the composition and size of the liquid metal particles are adjustable, and the liquid metal particles themselves are also easy to be compounded with other materials.
[0037] The present invention secondly selects hydrogel as the base material of the liquid metal alloy particles. Due to its high water content, it can also shield low-energy X-rays. At the same time, the liquid metal particles and hydrogel prepared by the present invention are non-toxic, and the composite material formed by the two has good biocompatibility.
[0038] The present invention prepares a liquid metal-hydrogel composite material through a simple preparation method. The liquid metal-hydrogel composite material not only has a certain flexibility and can adapt to application requirements of different shapes and surfaces, providing better fit and comfort, but also has the ability to be cut into any shape and can be personalized according to actual needs to provide better protection effect.
[0039] Tests have shown that the liquid metal-hydrogel composite material prepared by the present invention can be used as a patch and attached to the skin during radiation diagnosis and treatment to prevent normal skin tissue from being over-irradiated.
[0040] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. The specific implementation of the present invention is given in detail by the following embodiments and their accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of this application. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0042] Figure 1 The scanning electron microscope element analysis and melting point characterization diagram of the liquid metal alloy particles prepared in the embodiment of the present invention.
[0043] Figure 2 This is a physical picture of the hydrogel material prepared in the embodiment of the present invention.
[0044] Figure 3 This is a physical picture of the liquid metal-hydrogel composite material prepared in an embodiment of the present invention.
[0045] Figure 4 Graphs showing stress-strain curves and cyclic loading curves of the liquid metal-hydrogel composite material prepared in an embodiment of the present invention.
[0046] Figure 5 This is a rendering of the radiation protection performance of the liquid metal-hydrogel composite material prepared in an embodiment of the present invention.
[0047] Figure 6 This is a diagram showing the radiation protection performance of the liquid metal-hydrogel composite material prepared in an embodiment of the present invention when sheared into any shape. DETAILED DESCRIPTION
[0048] The preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings so that the purpose, features and advantages of the invention can be more clearly understood. It should be understood that the embodiments shown in the accompanying drawings are not intended to limit the scope of the present invention, but are only intended to illustrate the essential spirit of the technical solution of the present invention.
[0049] In the following description, certain specific details are set forth for the purpose of illustrating various disclosed embodiments to provide a thorough understanding of the various disclosed embodiments. However, those skilled in the relevant art will recognize that the embodiments may be practiced without one or more of these specific details. In other cases, well-known devices, structures, and techniques associated with the present application may not be shown or described in detail to avoid unnecessarily obscuring the description of the embodiments.
[0050] Unless the context requires otherwise, throughout the specification and claims, the word "comprise" and variations such as "include" and "have" should be construed in an open, inclusive sense, ie, should be interpreted as "including, but not limited to."
[0051] References throughout the specification to "one embodiment" or "an embodiment" indicate that a particular feature, structure, or characteristic described in connection with the embodiment is included in at least one embodiment. Thus, the appearances of "in one embodiment" or "in an embodiment" in various places throughout the specification are not necessarily all referring to the same embodiment. Furthermore, the particular features, structures, or characteristics may be combined in any manner in one or more embodiments.
[0052] As used in this specification and the appended claims, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise. It should be noted that the term "or" is generally employed in its sense including "and / or" unless the context clearly dictates otherwise.
[0053] In addition, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other. Unless otherwise specified, the reagents and materials used in the present invention are commercially available.
[0054] The present invention develops a liquid metal-hydrogel composite radiation protection material, which is prepared by the following method:
[0055] Step 1. Weigh metal indium (In, melting point 156.6° C.), tin (Sn, melting point 231.9° C.), and bismuth (Bi, melting point 271.3° C.) in a certain mass ratio, such as In:Sn:Bi=51:16.5:32.5.
[0056] In order to avoid oxidation loss during the smelting process, metal indium, tin and bismuth are placed in a flask in order from low to high melting points and mixed, and then glycerol is added to immerse the mixture of metal indium, tin and bismuth in the flask by 2-3 cm to avoid metal oxidation during heating.
[0057] Step 2: Place the flask containing the mixture of metal indium, tin, bismuth and glycerol in an argon atmosphere for a period of time, such as 5 minutes, to exhaust the air and avoid metal oxidation during heating.
[0058] Then continue to use a heating magnetic stirrer in an argon atmosphere, set the temperature to 275° C., set the magnetic stirring speed to 200 rpm, and stir at a low speed for 30 min.
[0059] The magnetic stirring speed was then adjusted to 1000 rpm, and high-speed stirring was performed for 5 minutes. Under the rapid stirring action, the large pieces of liquid metal in the flask were transformed into spherical liquid metal particles.
[0060] Step 3: After the bulk liquid metal in the flask turns into spherical liquid metal particles, take out the spherical liquid metal particles from the glycerol, and finally wash and dry them to obtain Bi 32.5 In 51 Sn16.5 Liquid metal alloy particles.
[0061] See also Figure 1 As shown, the Bi 32.5 In 51 Sn 16.5 Liquid metal alloy particle morphology, the results show that the obtained Bi 32.5 In 51 Sn 16.5 The size of the liquid metal alloy particles is in the range of 50-200 μm.
[0062] Then, Bi was characterized by elemental analysis 32.5 In 51 Sn 16.5 The synthesis of liquid metal alloy particles shows that the obtained Bi 32.5 In 51 Sn 16.5 The element composition of the liquid metal alloy particles is metal indium (In), tin (Sn), and bismuth (Bi).
[0063] Finally, the Bi 32.5 In 51 Sn 16.5 The melting point of the liquid metal alloy particles shows that the obtained Bi 32.5 In 51 Sn 16.5 The melting point of the liquid metal alloy particles is about 62°C, which is close to the melting point reported in the literature.
[0064] The above steps 1-3 can be used to prepare liquid metal alloy particles of different proportions. For example, the mass ratio can be adjusted to In:Sn:Bi=28:18:54 to prepare Bi 54 In 28 Sn 18 Liquid metal alloy particles; adjusting the mass ratio to In:Sn:Bi=50:40:10 to prepare Bi 10 In 50 Sn 40 Liquid metal alloy particles; adjusting the mass ratio to In:Sn:Bi=66.3:0:33.7 to prepare Bi 33.7 In 66.3 Liquid metal alloy particles, etc.
[0065] Step 4: Weigh polyvinyl alcohol and pure water to prepare a 15% PVA-H2O solution. The specific method is as follows:
[0066] First, polyvinyl alcohol with a molecular weight of 89000-98000 and pure water were mixed in a mass ratio of 15:85;
[0067] Then, a heating magnetic stirrer was used to stir at a temperature of 90°C and a magnetic stirring speed of 300 rpm;
[0068] After dissolution, a PVA-H2O solution with a mass fraction of 15% was obtained.
[0069] Step 5: Weigh polyvinyl alcohol and DMSO to prepare a 15% PVA-DMSO solution by mass fraction. The specific method is as follows:
[0070] First, polyvinyl alcohol with a molecular weight of 89000-98000 and DMSO were mixed in a mass ratio of 15:85;
[0071] Then, a heating magnetic stirrer was used to stir at a temperature of 90°C and a magnetic stirring speed of 300 rpm;
[0072] After dissolution, a PVA-DMSO solution with a mass fraction of 15% was obtained.
[0073] Before preparing the liquid metal-hydrogel composite material, the hydrogel material is first trial-made. The specific method is as follows:
[0074] First, 15% PVA-H2O solution and 15% PVA-DMSO solution were mixed and stirred in a mass ratio of 4:6, and then a high-power CNC ultrasonic cleaner was used to ultrasonicate the mixed solution of PVA-H2O solution and PVA-DMSO solution for 3 minutes to remove bubbles. Finally, the mixed solution of PVA-H2O solution and PVA-DMSO solution was poured into an acrylic mold of 5 cm × 5 cm × 2 mm, and placed in a refrigerator at -20°C for 2 minutes to form a gel. Figure 2 As shown, the hydrogel material is obtained.
[0075] Step 6: Mix 15% PVA-H2O solution and 15% PVA-DMSO solution in a mass ratio of 4:6 and stir evenly, then add the prepared Bi 32.5 In 51 Sn 16.5 The liquid metal alloy particles are stirred evenly. For example, 8 g of 15% PVA-H2O solution and 12 g of 15% PVA-DMSO solution are weighed. 32.5 In 51 Sn 16.5 20g of liquid metal alloy particles.
[0076] Step 7: Use a high-power CNC ultrasonic cleaner to ultrasonically clean the mixed solution of the PVA-H2O solution, the PVA-DMSO solution and the liquid metal alloy particles for 3 minutes to remove bubbles.
[0077] Step 8: Pour the mixed solution of the PVA-H2O solution, PVA-DMSO solution and liquid metal alloy particles from which bubbles have been removed into a 5 cm × 5 cm × 2 mm acrylic mold and freeze it in a -20°C refrigerator for 2 minutes to form a gel. Figure 3 As shown, the liquid metal content is 50% Bi 32.5 In 51 Sn 16.5 Liquid metal-hydrogel composites.
[0078] Next, the mechanical properties of the obtained liquid metal-hydrogel composite material are tested. The specific method is as follows:
[0079] See also Figure 4 As shown, the prepared liquid metal with a content of 50% Bi was tested using an electronic universal testing machine. 32.5 In 51 Sn 16.5 Mechanical properties of liquid metal-hydrogel composites, testing speed 50mm / min.
[0080] Tensile test results ( Figure 4 Left) shows that the liquid metal content is 50% Bi 32.5 In 51 Sn 16.5 The maximum elongation of the liquid metal-hydrogel composite material is about 447%, and the maximum tensile strength is about 0.907MPa.
[0081] The tensile test showed that the liquid metal contained 50% Bi. 32.5 In 51 Sn 16.5 The modulus of the liquid metal-hydrogel composite material is about 0.414MPa and the toughness is about 2.462MJ / m 3 .
[0082] At 100% strain, a cyclic loading test was carried out and the results ( Figure 4 Right) shows that the liquid metal contains 50% Bi 32.5 In 51 Sn 16.5 The hysteresis loop of the liquid metal-hydrogel composite material is the largest when it is cycled once, and it remains basically unchanged thereafter, and there is no obvious change in mechanical strength.
[0083] Finally, the radiation protection performance of the obtained liquid metal-hydrogel composite material was tested, and the specific method was as follows:
[0084] Set up a control group: cotton fabric, cut into a size of 5cm×5cm×2mm.
[0085] Experimental group setup: The prepared liquid metal content is 50% Bi 32.5 In 51 Sn 16.5 Liquid metal-hydrogel composite material, with dimensions of 5cm×5cm×2mm.
[0086] See also Figure 5 As shown, the control group ( Figure 5 Upper left) and experimental group ( Figure 5 The upper right) was attached to the hand, and the hospital's X-ray diagnostic machine (48keV, 3.1mAs) was used to measure the liquid metal content of 50% Bi in the control group and the experimental group. 32.5 In 51 Sn 16.5 Liquid metal-hydrogel composite material was imaged. The imaging results showed ( Figure 5 Lower left and Figure 5 Lower right), the liquid metal content is 50% Bi 32.5 In 51 Sn 16.5 Liquid metal-hydrogel composites have excellent radiation protection capabilities.
[0087] See also Figure 6 As shown, the prepared liquid metal content is 50% Bi 32.5 In 51 Sn 16.5 Liquid metal-hydrogel composites can be cut into any shape ( Figure 6 The hospital's X-ray digital subtraction angiography machine was then used to image the Figure 6 The imaging results show that the liquid metal content of 50% Bi can be cut into any shape. 32.5 In 51 Sn 16.5 Liquid metal-hydrogel composites have excellent radiation protection capabilities.
[0088] The above test experiments have proved that the liquid metal-hydrogel composite material prepared by the present invention can be used as a new type of lead-free radiation protection material for manufacturing lead-free radiation protection equipment required in the process of radiation diagnosis and treatment.
[0089] For example, the liquid metal-hydrogel composite material prepared by the present invention can be used as a patch and attached to the patient's skin during radiation diagnosis and treatment to prevent the patient's normal skin tissue from being over-irradiated.
[0090] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a liquid metal-hydrogel composite radiation protection material, characterized in that: The following steps are involved: Step 1, weighing metal indium, tin and bismuth in a certain mass ratio, and placing them in a flask in order of melting point from low to high, and then adding glycerol to immerse the mixture of metal indium, tin and bismuth in the flask by 2-3 cm; Step 2, placing the flask containing the mixture of metal indium, tin, bismuth and glycerol in an argon atmosphere for a period of time to expel air, and then continuing to stir the mixture in the argon atmosphere at a certain temperature using a heating magnetic stirrer for a period of time at a low speed, and then stirring the mixture at a high speed for a period of time, so as to cause the bulk liquid metal in the flask to become spherical liquid metal particles; Step 3, after the bulk liquid metal in the flask is transformed into spherical liquid metal particles, the spherical liquid metal particles are taken out from the glycerol, and finally washed with water and dried to obtain liquid metal alloy particles with a particle size in the range of 50-200 μm; Step 4, weigh polyvinyl alcohol and pure water to prepare a PVA-H2O solution with a mass fraction of 15%; Step 5, weigh polyvinyl alcohol and DMSO to prepare a PVA-DMSO solution with a mass fraction of 15%; Step 6, the prepared PVA-H2O solution and PVA-DMSO solution are mixed and stirred evenly according to a certain mass ratio, and then the prepared liquid metal alloy particles are added according to a certain mass ratio and stirred evenly; Step 7, using a high-power numerically controlled ultrasonic cleaner, ultrasonically treat the mixed solution of the PVA-H2O solution, the PVA-DMSO solution and the liquid metal alloy particles for a period of time to remove bubbles; Step 8: Pour the mixed solution of the PVA-H2O solution with bubbles removed, the PVA-DMSO solution and the liquid metal alloy particles into an acrylic mold of a specific size, and freeze it for a period of time to form a gel, thereby obtaining a liquid metal-hydrogel composite material with a certain liquid metal content.
2. The method for preparing the liquid metal-hydrogel composite radiation protection material according to claim 1, characterized in that: In step 1, the sum of the mass fractions of metal indium, tin, and bismuth is 100 parts. The mass ratio of indium, tin, and bismuth is adjusted to prepare liquid metal alloy particles with different proportions. The specific mass ratio includes but is not limited to the following options: In:Sn:Bi=51:16.5:32.5, used to prepare Bi 32.5 In 51 Sn 16.5 Liquid metal alloy particles; In:Sn:Bi=28:18:54, used to prepare Bi 54 In 28 Sn 18 Liquid metal alloy particles; In:Sn:Bi=50:40:10, used to prepare Bi 10 In 50 Sn 40 Liquid metal alloy particles; In:Sn:Bi=66.3:0:33.7, used to prepare Bi 33.7 In 66.3 Liquid metal alloy particles.
3. The method for preparing the liquid metal-hydrogel composite radiation protection material according to claim 1, characterized in that: In step 2, a flask containing a mixture of metal indium, tin, bismuth and glycerol is placed in an argon atmosphere and the air is exhausted for 5 minutes. The temperature of the heating magnetic stirrer is set to 275°C, the speed of the magnetic low-speed stirring is 200 rpm, the low-speed stirring time is 30 minutes, and the speed of the magnetic high-speed stirring is 1000 rpm, and the high-speed stirring time is 5 minutes.
4. The method for preparing the liquid metal-hydrogel composite radiation protection material according to claim 1, characterized in that: In step 4, the preparation method of PVA-H2O solution is: First, polyvinyl alcohol with a molecular weight of 89000-98000 and pure water were mixed in a mass ratio of 15:85; Then, a heating magnetic stirrer was used to stir at a temperature of 90°C and a magnetic stirring speed of 300 rpm; After dissolution, a PVA-H2O solution with a mass fraction of 15% was obtained.
5. The method for preparing the liquid metal-hydrogel composite radiation protection material according to claim 1, characterized in that: In step 5, the preparation method of PVA-DMSO solution is: First, polyvinyl alcohol with a molecular weight of 89000-98000 and DMSO were mixed in a mass ratio of 15:85; Then, a heating magnetic stirrer was used to stir at a temperature of 90°C and a magnetic stirring speed of 300 rpm; After dissolution, a PVA-DMSO solution with a mass fraction of 15% was obtained.
6. The method for preparing the liquid metal-hydrogel composite radiation protection material according to claim 1, characterized in that: In step 6, the mass ratio of PVA-H2O solution to PVA-DMSO solution is 4:
6. The mass ratio of the mixed solution of the PVA-H2O solution and the PVA-DMSO solution to the liquid metal alloy particles is 1:1 to prepare a liquid metal-hydrogel composite material with a liquid metal content of 50%.
7. The method for preparing the liquid metal-hydrogel composite radiation protection material according to claim 1, characterized in that: In step 7, the ultrasonic time of the high-power CNC ultrasonic cleaner is 3 minutes.
8. The method for preparing the liquid metal-hydrogel composite radiation protection material according to claim 1, characterized in that: In step 8, the freezing temperature of the mixed solution of the PVA-H2O solution, the PVA-DMSO solution and the liquid metal alloy particles is -20°C, and the freezing time is 2 minutes.
9. A liquid metal-hydrogel composite radiation protection material, characterized in that: The liquid metal-hydrogel composite radiation protection material is prepared by the preparation method of the liquid metal-hydrogel composite radiation protection material as described in any one of claims 1 to 8.
10. A use of a liquid metal-hydrogel composite radiation protection material prepared by the preparation method of a liquid metal-hydrogel composite radiation protection material as described in any one of claims 1 to 8 or a liquid metal-hydrogel composite radiation protection material as described in claim 9, characterized in that: As a lead-free radiation protection material, it is used to manufacture lead-free radiation protection equipment required in radiation diagnosis and treatment processes.
Citation Information
Patent Citations
Heat-conducting composite hydrogel containing liquid metal network and preparation method thereof
CN115716923A
Preparation method and application of polyvinyl alcohol / liquid metal hydrogel single-electrode flexible friction nano-generator
CN116566237A
Electromagnetic shielding composite aerogel as well as preparation method and application thereof
CN117164937A
Single-electrode liquid metal hydrogel-based friction nano-generator and preparation method thereof
CN118646289A
Method of producing metal spheres
GB925128A
Cited By
Flexible low-lead radiation shielding composite material and preparation method and application thereof
CN121650321A
A flexible low-lead radiation shielding composite material and a preparation method and application thereof
CN121650321B